2016
DOI: 10.3389/fpsyg.2016.01229
|View full text |Cite
|
Sign up to set email alerts
|

Music Regulators in Two String Quartets: A Comparison of Communicative Behaviors between Low- and High-Stress Performance Conditions

Abstract: In ensemble performances, group members use particular bodily behaviors as a sort of “language” to supplement the lack of verbal communication. This article focuses on music regulators, which are defined as signs to other group members for coordinating performance. The following two music regulators are considered: body gestures for articulating attacks (a set of movements externally directed that are used to signal entrances in performance) and eye contact. These regulators are recurring observable behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 22 publications
0
22
1
9
Order By: Relevance
“…The three videos were synchronized and combined into one video in post processing. Rating was done by external assessors, who coded the level of eye contact with a coding scheme on computerized software (Asan et al 2013) 55 Abele (1986), Allen and Guy (1977), Amerikaner (1980), Arnold et al (2000), Asan et al (2013Asan et al ( , 2015, Bavelas et al (2002, Berger andCunningham (1981), Biasutti et al (2016), Cary (1978), Cipolli et al (1989), Cohen et al (1989Cohen et al ( , 1991, Cordell and McGahan (2004 (1996), Podrouzek and Furrow (1988), Rutter et al (1978), Rutter (1976), Saenz and Alexander (2013), Schofield et al (2008), Schulz and Barefoot (1974), Sharpley and Sagris (1995), Stephenson et al (1973…”
Section: Event Recordermentioning
confidence: 99%
See 1 more Smart Citation
“…The three videos were synchronized and combined into one video in post processing. Rating was done by external assessors, who coded the level of eye contact with a coding scheme on computerized software (Asan et al 2013) 55 Abele (1986), Allen and Guy (1977), Amerikaner (1980), Arnold et al (2000), Asan et al (2013Asan et al ( , 2015, Bavelas et al (2002, Berger andCunningham (1981), Biasutti et al (2016), Cary (1978), Cipolli et al (1989), Cohen et al (1989Cohen et al ( , 1991, Cordell and McGahan (2004 (1996), Podrouzek and Furrow (1988), Rutter et al (1978), Rutter (1976), Saenz and Alexander (2013), Schofield et al (2008), Schulz and Barefoot (1974), Sharpley and Sagris (1995), Stephenson et al (1973…”
Section: Event Recordermentioning
confidence: 99%
“…Their behaviors were observed and their amount of eye contact while doing so was measured. Examples of natural behavior in the included studies are mothers breastfeeding their children (Arco et al 1979); patients visiting their physicians for a medical consultation (Asan et al 2013); waiting room behavior (Cary 1978); and musicians performing at a concert (Biasutti et al 2016). • Interview participants responded to a set of questions asked by an interviewer, researcher, or confederate.…”
Section: Participant Behavior In the Included Studiesmentioning
confidence: 99%
“…For now, let us begin with a comparison between the verbal communication occurring between musicians, composers, or improvisers when planning, rehearsing, optimizing, or simply sharing information about a novel piece or performance (see e.g., Clarke et al, 2013 , 2016 ; Biasutti, 2015 , 2018 ) and the online patterns of non-verbal interaction and self-regulation exhibited by members of classical ensembles (see e.g., Davidson and Good, 2002 ; Biasutti et al, 2016 ). In both cases, outcomes can be hardly predicted with precision: complaints or suggestions voiced by instrumentalists regarding particularly complex musical configurations, for example, may change the composer’s initial plans in various ways, giving rise to a series of adaptive, constructive dialogues, in which a middle ground between the composer’s expressive needs and the performative constraints indicated by the performer is generally reached 2 (see Doffman and Calvin, 2017 ; Whittall, 2017 ).…”
Section: Musical Creativity Beyond Solo Andmentioning
confidence: 99%
“…It has also been found that the frequency of visual contact among string quartet players did not change in relation to the stress associated with the performance setting, i.e. rehearsal setting vs. public recital (Biasutti et al, 2016 ). A number of studies have revealed that visual cues improve the communication of interpersonal intentions between musicians (Dahl and Friberg, 2007 ; Castellano et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%